The legislature and agenda politics of social welfare: a comparative analysis of authoritarian and democratic regimes in South Korea. Issue 7 (3rd October 2019) - Shim, Jaemin
ABSTRACT: The article mainly seeks to explain the legislature's preferences in social welfare before and after democratization using South Korea as a case study. Based on an original dataset that consists of all executive and of legislative branch-submitted bills between 1948 and 2016 – roughly 60, 000– legislative priority on social welfare is compared over time, and tested using logistic regressions. The key focus of analysis is whether and how the level of democracy affected the degree and universality of social welfare priority. The findings show that the promotion of social welfare is positively related to higher levels of democracy in a continuous fashion, which clearly points to the need to avoid applying a simple regime dichotomy – authoritarian or democratic – when seeking to understand social welfare development. Going further, the article examines the legislature's priority in welfare issues within a presidential structure and under majoritarian electoral rule, at different levels of democracy. The result shows that the higher levels of democracy are, the more the legislative branch contributes to the overall salience of social welfare legislative initiatives as compared to the executive branch. Moreover, the legislative branch itself prioritizes a social welfare agenda – alongside democratic deepening – over other issues.